Dymanics of matrix-metalloproteinase 9 after brain trauma--results of a pilot study - Kolar, Martin; Pachl, Jan; Tomasova, Helena; Haninec, Pavel (Acta neurochirurgica. Supplement, 2008)
BACKGROUND: Secondary brain injury contributes to poor outcome for patients sustaining brain trauma. Matrix metalloproteinase-9 (MMP-9) is a potential marker, as well as effector of secondary brain injury. This enzyme degrades components of extracellular matrix, and thus it can contribute to blood-brain barrier disruption. METHODS: We studied dynamics of MMP-9 in jugular venous blood of 15 patients sustaining either an isolated head injury or a head injury as a part of major trauma, and requiring intensive care (Glasgow Coma Scale <8 at the time of admission). Blood samples were taken at the 1st, 3rd and 5th day, levels of MMP-9 in plasma were assessed using ELISA. Outcome quality was assessed at the time of discharge from our hospital. FINDINGS: Our results show an increase of MMP-9 levels on the 1st day after the brain trauma, followed by a drop on the 3rd day and a rise on day 5. This biphasic time-course was observed in all patients, but no statistically significant differences between each group (major trauma vs. isolated brain trauma, good outcome vs. poor outcome) were found. CONCLUSIONS: Initially increased MMP-9 levels in the 1st posttraumatic day is probably related to transient blood-brain barrier dysruption. The decrease of MMP-9 levels observed on the 3rd day can be explained by restoration of blood-brain barrier integrity and its reduced permeability. The second rise of MMP-9 levels observed in the 5th day probably indicates a developing secondary brain injury during which MMP-9 is produced in the brain as a part of an inflammatory response. RESULTS: of our study suggest that MMP-9 could play an important role in pathogenesis of secondary brain injury.
Keywords: dospělí; senioři nad 80 let; Pilot Projects; Humans; Matrix Metalloproteinase 9; lidé středního věku; Glasgowská stupnice kómat; Middle Aged; Aged, 80 and over; Young Adult; mladý dospělý; Time Factors; ELISA; mužské pohlaví; Enzyme-Linked Immunosorbent Assay; Nonlinear Dynamics; Adult; poranění mozku; časové faktory; nelineární dynamika; ženské pohlaví; Brain Injuries; lidé; Glasgow Coma Scale; pilotní projekty; Aged; senioři; Male; matrixová metaloproteinasa 9; Female